2007
DOI: 10.1002/ijc.23122
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan oligosaccharides sensitize lymphoma resistant cell lines to vincristine by modulating P‐glycoprotein activity and PI3K/Akt pathway

Abstract: Multidrug resistance (MDR) is one of the main reasons for failure of cancer therapy. It may be mediated by overexpression of ATPdependent efflux pumps or by alterations in survival or apoptotic pathways. Fragments generated by enzymatic degradation of hyaluronan (oHA) were able to modulate growth and cell survival and sensitize MDR breast cancer cells to cytotoxic drugs. In this work the relationship between oHA and MDR in lymphoid malignancies was analyzed using murine lymphoma cell lines resistant to doxorub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…When hyaluronan oligosaccharides inhibit the interaction between hyaluronan and cancer cells, PI3K/Akt survival signaling in vitro is suppressed, and tumor growth in vivo is reduced (Ghatak et al 2002). Hyaluronan oligosaccharides also modulate MDR in lymphoma cells by decreasing the phosphorylation of Akt and P-glycoprotein activity (Cordo-Russo et al 2008). Furthermore, hyaluronan oligosaccharide treatment decreases BCRP expression and inhibits Akt activation in malignant glioma cells (Gilg et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…When hyaluronan oligosaccharides inhibit the interaction between hyaluronan and cancer cells, PI3K/Akt survival signaling in vitro is suppressed, and tumor growth in vivo is reduced (Ghatak et al 2002). Hyaluronan oligosaccharides also modulate MDR in lymphoma cells by decreasing the phosphorylation of Akt and P-glycoprotein activity (Cordo-Russo et al 2008). Furthermore, hyaluronan oligosaccharide treatment decreases BCRP expression and inhibits Akt activation in malignant glioma cells (Gilg et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that long-term treatment of genistein could induce the related protein expression of first-pass metabolism in mice [14,15] and the activities of phase II metabolic enzymes in mice could be mediated by oligosaccharides [13,16,17]. Moreover, some non-digestible carbohydrates, such as hyaluronan oligosaccharides and astragalus polysaccharides, were shown to inhibit P-gp, MRP1, and MRP2 expression, thereby contributing to an increase in intracellular concentration of food ingredients or drugs [18,19]. Accordingly, we suppose that stachyose promoting absorption of genistein may be closely related to inhibition of first-pass metabolism of genistein in the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that many cancer chemopreventive agents are known to lower cancer risk by suppressing HA/CD44-signaling pathway (Bourguignon et al , 2009; Cordo Russo et al , 2008), which subsequently leads to attenuation of pro-inflammatory mediators and their activities. Natural anti-oxidants like ITSCs found in cruciferous vegetables have been under investigation due to their potential anti-cancer effects.…”
Section: Resultsmentioning
confidence: 99%